EUROASIAN IDEA IN KAZAKHSTAN POLICY: THEORY AND PRACTICE - R. S. Faizova (Модернизация, инновация, развитие)
After disintegration of the USSR, the euroasian idea known since 1920–1930-th, got transformed on the initiative of N. Nazarbayev, President of the Republic of Kazakhstan, into a constructive geopolitical doctrine that provides for a new mechanism of stepwise political and economicalintegration of post-soviet states. Main aims of the euroasian union creation project were to provide for economic gains and safety to every participant thereof as well as to prevent division of the post-soviet space into Orthodox Christian and Islamic states and regions. Practical implementation of the euroasian ideas and respective efforts became Euroasian Economic Association (EvrAsES) formed by Russia, Kazakhstan, Belarus, Kyrgyzstan and Tajikistan. By today, the euroasian idea has not yet been realized at full scale; long finishing work is ahead.